The Price of a Better Catch : Valuing Fishing Improvements in Norrbotten through the Contingent Valuation and the Travel Cost Method - Hilmersson, Gustav; Hallberg, Elin (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2025)
This study aimed to estimate the willingness to pay for improved fishing and the consumer surplus fishermen had at the Lule River in 2023. The study limited itself to examining only recreational fishermen to investigate the purpose. The contingent valuation method was applied to measure the willingness to pay for improved fishing, and the travel cost method was used to estimate the consumer surplus from the current fishing. A total of 429 responses were collected, of which 168 were used for the analysis. The study found a positive willingness to pay for improved fishing of, on average, approximately SEK 496. Variables that significantly impacted the willingness to pay were the frequency of visits, household members, age, education, income, and travel costs, all of which had a positive impact. The average consumer surplus per person was estimated to be approximately SEK 4,920. Samhällsekonomisk analys av frågeställningar kring omprövningen av vattenkraft